Knowledge, attitude and practices of physicians on home care in Ninh Kieu District, Can Tho City, Vietnam, 2007 - Thai Thi Ngoc Thuy. (Thesis--(Master of Science in Clinical Medicine)-- University of the Philippines Manila.)
Background:Home health care offers a more holistic approach in caring for patients than other health services. It is best given to elderly, and patients with chronic illness, disability, HIV/AIDS, cancer, and acute problems. It offers physician a good physician-patient relationship and continuing care after discharging patients to their home. While developing rapidly in many countries, it is still slow in both practice and training on home care in Vietnam. It will be a basis for the establishment of a home care program and improving the curriculum in which physicians are trained on knowledge and skills to provide home health care. Objective: To determine the knowledge, attitude and practice of physicians on home care in Nihn, Kiue District, Can Tho City, Vietnam. Method: This study was done through combination of two phases-qualitative survey and cross-sectional design. The quality survey included 5 interviews, 2 focus group discussions while the pre-test with 72 respondents was conducted to develop questionnaire for phase 2. In the second phase, all 188 graduate and post-graduate physicians selected by a systematic random sampling from all 11 hospitals, 13 commune health centers and 16 private clinics answered a 40-item self-administered questionnaire. The four dimensions measured were Socio-demographics, Knowledge, Attitude and Practice on home care. Statistical analysis: The questionnaire was developed as a result on phase 1 and reliability was assessed based on Cronbach's alpha coefficient. The qualitative data were recorded, transcribed and analyzed manually. All qualitative data were encoded and analyzed using SPSS version 12.0.1. Percentage analysis, T test and Chi-square to describe socio-demographic characteristics, knowledge, attitude and practices of physicians on home care as well as to determine the relationships between these variables. Results: A total of 5 interviews, 2 focus group discussions, and 72 respondents in phase 1 and 188 physicians in phase 2 were interviewed. A self administered semi structure questionnaire with 40 items was developed as a result of phase 1. The results of phase 2 showed that 69.1% of 188 physicians had good knowledge of definition, advantages, types of services and physicians' roles in home care. 73.4% of physicians agreed when asked 7 attitude questions relating to whether (1) A home care program linked by various specialties and coordinated by family physicians should be established to improve health care for the community and (2) Home care program should be incorporated in graduate and postgraduate curriculum. In practice, 39.4% of physicians have done home care. There were associations between knowledge and attitude towards home care (P=0.007 < 0.05). Statistically significant associations were the once between Need for additional training on home care and Age as well as and Post-graduate degree (P=0.01 and 0.013 < 0.05, respectively. In addition, Intention to practice home care in the future also statistically significantly associated with Age Post-graduate and Number of years in home care practice (P=0.01, 0.001, 0.0001 < 0.05 respectively). Conclusion and Recommendation: There was a relatively high rate of physicians with good knowledge (69.1%) and positive attitude (73.4%) toward home care. In clinical practice, a program of home care linked by various specialties with medial and non medical members and coordinated by family physicians should be established to improve health care for the community. In the academic setting, home care program should be incorporated in graduate and postgraduate curriculum.
Keywords: Physicians -- Attitudes; Physicians -- Vietnam